(untitled) (Revista Argentina de Musicología, 2020)
This article proposes that the processes of organizing music festivals have the potential to generate instances that widen the margin of agency of some sectors of society, specifically that of the participating musicians and some related communities. Based on a concept of agency that integrates the tenets of Anthony Giddens, Marilyn Strathern and Norman Long, the article analyzes the case of the Petronio Álvarez Pacific Music Festival, an event focusing on traditional Afro-Colombian music that has been held since 1997 in the city of Cali (Colombia). Specifically, it discusses the changes that took place within the process of curating the music during the first years of the festival and the tension between economic and social development that remains to this day. The analysis concludes that the Petronio Álvarez festival has generated spaces in which there is a permanent “give and take” between different social actors, and that it is a junction between a broad community of producers and fans of traditional music of the region. The article gathers more than ten years of the authors’ experiences as festival goers, musicians, jurors and members of the organization.